Periprocedural Outcomes Comparing Fibroid Embolization and Focused Ultrasound: A Randomized Controlled Trial and Comprehensive Cohort Analysis. Issue 9 (September 2017) - Barnard, Emily P.; AbdElmagied, Ahmed M.; Vaughan, Lisa E.; Weaver, Amy L.; Laughlin-Tommaso, Shannon K.; Hesley, Gina K.; Woodrum, David A.; Jacoby, Vanessa L.; Kohi, Maureen P.; Price, Thomas M.; Nieves, Angel; Miller, Michael J.; et al.
Abstract : (Abstracted from Am J Obstet Gynecol 2017;216:500.e1–500.e11) Although uterine fibroids are a common problem among reproductive-aged women, few comparative effectiveness studies are available to guide treatment decisions. Two minimally invasive treatments—uterine artery embolization (UAE) and magnetic resonance imaging–guided focused ultrasound surgery (MRgFUS)—have been approved by the US Food and Drug Administration for treatment of symptomatic uterine fibroids.